Spatial Distribution of Mangrove Density Using Sentinel-2a Imagery of Perancak Estuary - Pratama, Gede Agus Surya; Suryani, Sang Ayu Made Putri; Arya, I Wayan (Formosa Journal of Sustainable Research, 2024)
Mangrove forest ecosystems are vegetative communities found in tropical and subtropical estuaries and shallow coastal lagoons. They are mostly composed of several types of mangrove trees that can thrive in muddy beach tidal zones. The science and art of remote sensing involves analyzing data collected using instruments without coming into direct touch with the thing, location, or phenomena being researched in order to learn more about it. Sentinel-2A is a medium spatial resolution satellite image with a wide swath that can be used for studies on land cover monitoring, including vegetation, soil, and water, as well as water networks and coastal areas. It revisits the same location every 5 days, as opposed to Landsat's 16-day interval. The research findings indicate that there was an increase in the development of mangrove density between 2019 and 2023. Specifically, the total area of mangrove forests rose from 118.59 Ha in 2019 to 145.44 Ha in 2023. These developments are displayed in the table below